2014
DOI: 10.1186/1471-2458-14-248
|View full text |Cite
|
Sign up to set email alerts
|

Non-paying partnerships and its association with HIV risk behavior, program exposure and service utilization among female sex workers in India

Abstract: BackgroundIn India, HIV prevention programs have focused on female sex workers’ (FSWs’) sexual practices vis-à-vis commercial partners leading to important gains in HIV prevention. However, it has become apparent that further progress is contingent on a better understanding of FSWs’ sexual risks in the context of their relationships with non-paying partners. In this paper, we explored the association between FSWs’ non-paying partner status, including cohabitation and HIV risk behaviors, program exposure and ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…Analogous to intimate partnerships in other contexts, unprotected sex by SWs’ intimate partners is common relative to by clients (Deering et al, 2011; Murray et al, 2007; Travasso et al, 2014), even when SWs are aware of their intimate partner’s drug use and sexual risk behaviors for HIV/STIs (El-Bassel and Wechsberg, 2012; El-Bassel et al, 2010; Pequegnat and Bray, 2012). Moreover, SWs in our study reported that 11.2% of intimate partners had sexual relationships with other SWs and 14.3% had sexual relationships with other non-SW female partners, suggesting complex pathways through which HIV and STIs could potentially be contracted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous to intimate partnerships in other contexts, unprotected sex by SWs’ intimate partners is common relative to by clients (Deering et al, 2011; Murray et al, 2007; Travasso et al, 2014), even when SWs are aware of their intimate partner’s drug use and sexual risk behaviors for HIV/STIs (El-Bassel and Wechsberg, 2012; El-Bassel et al, 2010; Pequegnat and Bray, 2012). Moreover, SWs in our study reported that 11.2% of intimate partners had sexual relationships with other SWs and 14.3% had sexual relationships with other non-SW female partners, suggesting complex pathways through which HIV and STIs could potentially be contracted.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a study in India found that between 7–12% of SWs reported inconsistent condom use with occasional clients, while 58–97% reported inconsistent condom use with intimate partners (Travasso et al, 2014). Among SWs in a US study, 56% reported always using condoms with their clients, compared to 32% and 14% with occasional partners and regular partners, respectively (Johnson et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
“…However, condomless sex with clients may not be the only source of HIV/STI risk for FSWs (Travasso, Mahapatra, Saggurti, & Krishnan, 2014). Many FSWs report having noncommercial male partners (Deering et al, 2011; Hong & Li, 2008; Mishra et al, 2013), with whom condom use is infrequent (Hong & Li, 2008; Travasso et al, 2014; Ulibarri et al, 2012; Voeten, Egesah, Varkevisser, & Habbema, 2007). A study by Lowndes et al (2000) in Benin, Africa found a greater percentage of FSWs’ boyfriends were HIV positive compared to their clients (16.1% vs. 8.5%).…”
Section: Fsws’ Condom Use With Clients and Intimate Partnersmentioning
confidence: 99%
“…Only two Indian studies have considered the multi-dimensional nature of vulnerability by creating a composite index of vulnerability. One of these studies considered three factors (solicitation in street-based setting, experience of violence and financial debt) to create a composite measure of vulnerability [ 15 ]. The other study considered six factors (literacy, duration in sex work, mobility for sex work, an additional source of income other than sex work, currently being in debt, and having children) to create an index of vulnerability.…”
Section: Introductionmentioning
confidence: 99%